Three-dimensional pulse-width modulation technique in three-level power inverters for three-phase four-wired system. - Man-Chung Wong (IEEE Transactions on power electronics)
Shunt-connected trilevel power inverter in three-phase four-wired system as an active filter or individual current supply (peak-load supply) is studied by a novel technique: three-dimensional (3-D) voltage vectors pulse width modulation (PWM). In past decades, almost all the study for PWM is limited to the two-dimensional (2-D) domain, α and β frames, in a three-phase three-wired system. However, in practical operation, there are many three-phase four-wired systems in distribution sites. The generalized study of 3-D two-level and three-level inverters is achieved in this paper so as to perform the basic theory of 3-D multilevel space vector switching PWM technique. The sign cubical hysteresis control strategy is proposed and studied with simulation results in 3-D aspect. The 3-D PWM technique in three-level inverters is accomplished